Knowledge of ethnoveterinary medicine in the Province of Granada, Andalusia, Spain. - Benítez, Guillermo; González-Tejero, M. Reyes; Molero-Mesa, Joaquín (Journal of ethnopharmacology, 2012)
This paper constitutes an important contribution to the knowledge of biological resources used in ethnoveterinary practices (EVPs) in southern Europe, a territory with a clear lack of information on the subject. Aim of the study: To catalogue, analyze, and disseminate the knowledge of plant and animal use in eth- noveterinary practices in the province of Granada. Data have been analyzed to highlight the similarities between ethnoveterinary practices and human ethnopharmacology for the same study area. Methodology: Information was gathered through open and semi-structured interviews with local people, mainly elderly shepherds and farmers, in the western part of the province. The primary data have been supplemented with information on EVPs from previous ethnobotanical works for the province. Data were gathered using the same field methods. Results: A total of 88 ethnoveterinary uses are documented for the treatment of 24 animal conditions. Of these, 82 uses involve 60 different plant species. Over three-quarters of these plants are also used for some human conditions in the same study area. Moreover, 6 animal species were catalogued for 6 other ethnoveterinary uses; four of these species were also used for similar conditions in humans. Ritual and health-prevention practices are also discussed. Conclusions: EVPs in southern Spain involve a high number of species and conditions and are strongly linked to folk tradition (i.e. how local people understand certain conditions and their treatment, some- times in a ritual manner). Unfortunately, some evidence of their slow disappearance has been found.
The following values have no corresponding Zotero field: publisher: Elsevier Ireland Ltd accession-num: 22155471
Keywords: Ethnoveterinary; Granada; Spain; Veterinary medicine; Zootherapy

Ethnobotany of Montseny biosphere reserve (Catalonia, Iberian Peninsula): plants used in veterinary medicine. - Bonet, M Angels; Vallès, Joan (Journal of ethnopharmacology, 2007)
The present paper deals with plants used in veterinary medicine in Montseny. An ethnobotanical survey was carried out in the Montseny massif, which is situated in north-east Catalonia (Iberian Peninsula), covers 826 km(2) and has a population of 80,000. The information was obtained through 120 ethnobotanical interviews to 180 informants. Out of 584 species reported, 351 are claimed to be used in the health field (human and veterinary medicine), 280 in human and animal food and 236 have another kind of popular use. Medicinal species represent around 16.5% of Montseny's vascular flora. In a previous paper we addressed plant use in human medicine, and the present paper deals with veterinarian uses. As a reflection of the importance of rural life in the region, at least until recent times, a substantial number of medicinal plants (89 species, representing 6% of the flora of the territory and 6.4% of all medicinal use-reports in the region) is used in veterinary medicine. These remedies are mostly for cows, calves, sheep, pigs and horses, and secondarily, to poultry, rabbits and dogs. The main ailments treated are postnatal problems, intestinal troubles, wounds and dermatological problems. In many cases, the use of these remedies in veterinary medicine is fully consistent with their use in human medicine.
Keywords: Catalonia; Ethnobotany; Ethnoveterinary; Medicinal plants; montseny; Traditional knowledge

Ethnobotany of Montseny biosphere reserve (Catalonia, Iberian Peninsula): plants used in veterinary medicine. - Bonet, M. Angels; Vallès, Joan (Journal of ethnopharmacology, 2007)
The present paper deals with plants used in veterinary medicine in Montseny. An ethnobotanical survey was carried out in the Montseny massif, which is situated in north-east Catalonia (Iberian Peninsula), covers 826 km(2) and has a population of 80,000. The information was obtained through 120 ethnobotanical interviews to 180 informants. Out of 584 species reported, 351 are claimed to be used in the health field (human and veterinary medicine), 280 in human and animal food and 236 have another kind of popular use. Medicinal species represent around 16.5% of Montseny's vascular flora. In a previous paper we addressed plant use in human medicine, and the present paper deals with veterinarian uses. As a reflection of the importance of rural life in the region, at least until recent times, a substantial number of medicinal plants (89 species, representing 6% of the flora of the territory and 6.4% of all medicinal use-reports in the region) is used in veterinary medicine. These remedies are mostly for cows, calves, sheep, pigs and horses, and secondarily, to poultry, rabbits and dogs. The main ailments treated are postnatal problems, intestinal troubles, wounds and dermatological problems. In many cases, the use of these remedies in veterinary medicine is fully consistent with their use in human medicine.
The following values have no corresponding Zotero field: accession-num: 17059874
Keywords: Catalonia; Ethnobotany; Ethnoveterinary; Medicinal plants; montseny; Traditional knowledge